2011
DOI: 10.1371/journal.pone.0029166
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Cell Specific Deletion of Dicer1 Leads to Defective Insulin Secretion and Diabetes Mellitus

Abstract: Mature microRNAs (miRNAs), derived through cleavage of pre-miRNAs by the Dicer1 enzyme, regulate protein expression in many cell-types including cells in the pancreatic islets of Langerhans. To investigate the importance of miRNAs in mouse insulin secreting β-cells, we have generated mice with a β-cells specific disruption of the Dicer1 gene using the Cre-lox system controlled by the rat insulin promoter (RIP). In contrast to their normoglycaemic control littermates (RIP-Cre+/− Dicer1 Δ/wt), RIP-Cre+/− Dicer1f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 42 publications
7
110
1
Order By: Relevance
“…Dicer1-depleted mice exhibited reduced insulin gene expression and impaired insulin secretion, both of which preceded the development of progressive hyperglycemia and diabetes. These animals also showed altered islet cell morphology, reduced β-cell mass, and differential pancreatic islet morphology, although fetal and neonatal β-cell development and insulin secretory function were normal [24,26]. Thus, despite normal β-cell development, disruption of the miRNA network effectively resulted in defective insulin secretion, hyperglycemia, and diabetes, implying a significant function for miRNAs in this cell type.…”
Section: Mirnas Involved In the Regulation Of Pancreatic β-Cell Functionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dicer1-depleted mice exhibited reduced insulin gene expression and impaired insulin secretion, both of which preceded the development of progressive hyperglycemia and diabetes. These animals also showed altered islet cell morphology, reduced β-cell mass, and differential pancreatic islet morphology, although fetal and neonatal β-cell development and insulin secretory function were normal [24,26]. Thus, despite normal β-cell development, disruption of the miRNA network effectively resulted in defective insulin secretion, hyperglycemia, and diabetes, implying a significant function for miRNAs in this cell type.…”
Section: Mirnas Involved In the Regulation Of Pancreatic β-Cell Functionmentioning
confidence: 95%
“…Aberrant regulation of miRNAs has been associated with the development of many diseases including neurologic disorders, cardiovascular diseases, and certain cancers [22,23]. miRNAs have also been found to be critical for pancreatic development [24][25][26], maintenance of β-cell identity [27], and regulation of biological processes related to T2D pathogenesis, including glucose-stimulated insulin secretion, glucose uptake in muscle and liver, adipogenesis, and adipocyte function [28][29][30].…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…86 miRNAs control insulin synthesis and secretion β-cell-specific ablation of Dicer1 can result in the onset of diabetes as a consequence of impaired insulin biosynthesis and glucose-stimulated insulin secretion (GSIS). [87][88][89] Recent studies have indicated that Ago2 is also critical for the insulin-secreting capacity and compensatory expansion of β-cells. 90 Deletion of Ago2 in insulin-producing β-cells (the MIN6 cell line) enhances insulin production.…”
Section: Mirnas: Participants In Autoimmunity-mediated β-Cell Damagementioning
confidence: 99%
“…RIP-Cre-Dicer1 flox/flox mice exhibit normal beta cell formation during fetal and neonatal life, but become progressively hyperglycaemic and finally develop overt diabetes in adulthood. These mice display defects in islet number, size and architecture, in beta-cell mass, and in insulin biosynthesis and secretion [9,10]. Loss of Dicer1 in the adult does not affect total beta cell mass, but results in insufficient insulin biosynthesis and release in response to glucose, causing hyperglycaemia in both fed and fasted states [11].…”
Section: Micrornas As Regulators Of Beta Cell Differentiation and Funmentioning
confidence: 99%